Toward Further Understanding of Crohn’s Disease-Related Fatigue: The Role of Depression and Emotional Processing - Banovic, Ingrid; Montreuil, Louise; Derrey-Bunel, Marie; Scrima, Fabrizio; Savoye, Guillaume; Beaugerie, Laurent; Gay, Marie-Claire (Frontiers in Psychology, 2020)
Because the relationship between Crohn’s Disease (CD) activity and CD-related fatigue remains poorly understood, this study investigated the role of underlying psychological processes (depression, anxiety and emotional processing). It was expected that the relationship between CD activity and CD-related fatigue would be mediated by depression and anxiety and also by a deficit in emotional processing. This prediction was tested in 110 CD patients who completed self-report questionnaires assessing fatigue (FSS), clinical activity of Crohn’s Disease (HBAI), psychological suffering (HADS) and emotional processing (EPS-25). A path analysis showed both direct and indirect effects in the relationship between Crohn’s Disease activity and CD-related fatigue, accounting for 33% of the variance. One indirect effect on the experience of fatigue was depression, but there was no effect of anxiety. These preliminary results confirm that disease activity induces an increase in depressive symptoms, which in turn leads to an increase in the level of fatigue. The most novel result of the present study is that emotional processing had an indirect effect on the relationship between Crohn’s Disease (CD) and CD-related fatigue: when the disease was more active, patients exhibited greater disruption of emotional processing, which in turn led to greater fatigue. The results did not reveal any association between depression and emotional processing. In conclusion, this work highlights the role of emotional processing in CD-related fatigue and the importance of taking this factor into account in order to manage this condition better.